REPORTING ANIMAL RESEARCH −ARRIVAL OF ‘ARRIVE’ - Khan, Muhammad Alamgir (Pakistan Journal of Physiology, 2013)
Reporting of in vivo animal research in a befitting way is the responsibility of the researcher. Inadequate reporting not only raises ethical and scientific concerns but also makes difficult for other researchers to comprehend and replicate the research process. NC3Rs developed ARRIVE guidelines for reporting animal research. It is the joint responsibility of all stakeholders like authors, journal editors, peer reviewers, publishers, and funding bodies to disseminate, endorse, and apply ARRIVE guidelines to get real benefit out of them. With this editorial, Pakistan Journal of Physiology endorse the ARRIVE guidelines and encourages the authors to follow these guidelines while designing and reporting their research projects. We also prompt the peer reviewers to keep in mind the ARRIVE guidelines when evaluating the publications involving animal research. We trust, by adhering to these guidelines, the quality of research projects and publications involving in vivo experiments on animals, will improve. Pak J Physiol 2013;9(2):1–2